Visual Outcome after Cataract Surgery in Phacolytic Glaucoma - Islam, Mohammad Ariful; Rasul, Mohammad Ghulam; Haque, SM Enam ul; Chowdhury, Faisal Quader Shah; Alam, Afroza E; Hossain, Mohammad Farid; Hasan, Mohammad Rashedul; Mistry, Polash Kanti (Community Based Medical Journal, 2022)
A prospective study was conducted between March 2021 and February 2022 in the National Institute of Ophthalmology & Hospital, Dhaka, Bangladesh involving 30 patients who underwent cataract surgery for phacolytic glaucoma. The aim of this study was to see the postoperative visual outcome of cataract surgery in patients with phacolytic glaucoma. Visual acuity and development of any postoperative complications were recorded. The mean age of the patients was 60.7 years. Female to male ratio was 1.3:1. Most of the patients (67%) presented after 1 week of symptoms. On the first visit, mean preoperative intraocular pressure (IOP) was 37.5 mm of Hg. Following surgery, 93.33% had an intraocular pressure less than 21 mm Hg at discharge. Visual acuity (VA) as perception of light (PL) was found doubtful in 2 (6.67%), while PL was positive in 17 (56.66%) and HM <3/60 was in 11 (36.66%) preoperatively. At discharge, 73.33% achieved VA 6/24 or better, 5 (16.67%) had less than 6/24 and 3 (10%) less than 3/60. Cataract surgery is effective to restore visual acuity and lowering the intraocular pressure (IOP) in patients with phacolytic glaucoma. CBMJ 2022 July: vol. 11 no. 02 P: 120-124